Identifying the Relationship between Entrepreneurship and Strategic Management - Valliappan Raju, Assoc. Prof. Dr.; Md Rom Bin Tamjis, Prof Dr. (International Journal of Engineering and Technology, 2019)
Key enterprise depends on the mix of business enterprise and key administration. Key enterprise is another methodology in the executives writing. Additionally, the present business world requires an introduction towards key enterprise. Vital business is likewise a need for organizations to make most extreme riches. In this examination, vital enterprise that is the crossing point of business and vital administration is broke down.Â Â